Measuring Distribution of Intellectual Capital Components Contribution: French Context - Pap, Endre; Petković, Miloš; Simićević, Ana (The European Journal of Applied Economics, 2021)
In this paper the contribution of intellectual capital components (human capital, structural capital and relational capital) in the overall intellectual capital value is investigated. This paper adopted quantitative statistical methods Lambda phase measurement and Shapley’s value on the sample of 498 French companies in the period of 2008 to 2016 in order to estimate the highest and lowest contributions of intellectual capital components. For the purpose of the study, the official financial information from the companies’ annual reports were taken from the financial database “Point Risk”. The paper concentrates on two out of three intellectual capital components: structural and customer capital components. By the Shapley’s value final result, the greatest importance has the customer capital component, which represents company’s commercial activities with the coefficient of 0.29911. On the other side, the lowest importance has the structural capital component that represents value coming from research and development expenses with the coefficient of 0.07463 This study contributes to the management sciences literature by examining distribution of contribution of three intellectual capital components in the annual reports of French companies.